A system biology study of BALF from patients affected by idiopathic pulmonary fibrosis (IPF) and healthy controls. Issue 11 (22nd October 2014) - Landi, Claudia; Bargagli, Elena; Carleo, Alfonso; Bianchi, Laura; Gagliardi, Assunta; Prasse, Antje; Perari, Maria G.; Refini, Rosa M.; Bini, Luca; Rottoli, Paola; Everett, Allen; Ignjatovic, Vera
<x xml:space="preserve">Abstract</x> Background Idiopathic pulmonary fibrosis (IPF) is a devastating interstitial lung disease characterized by progressive loss of the alveolar integrity, recruitment, and activation of myofibroblast, and excessive collagen deposition that resulted in loss of parenchymal architecture and lung function. Although etiology is unknown, major risk factor of disease development is represented by cigarette smoke or exposure to dust. Aims Aim of this proteomic study was to compare broncho alveolar lavage fluid protein profiles of IPF patients, never‐smoker healthy control (nonsmoker control) and smoker control subjects in order to investigate proteins potentially related to disease progression and pathogenesis. Methods Broncho alveolar lavage fluid samples were resolved using 2D‐PAGE and the differentially expressed proteins were identified by MS. The performed PCA statistically proved the correlation existing between differentially expressed spots in the three groups. Functional analysis of the identified proteins was performed by pathway and enrichment analysis by MetaCore and Database for Annotation, Visualization and Integrated Discovery. Results Interestingly, transcriptional factors NF‐kB, PPARγ, and c‐myc emerged as well as a group of functional hubs. Enrichment analysis suggested that Gene Ontology (GO) process networks and pathway maps involved in IPF included angiotensin system maturation, renin‐angiotensin‐aldosteron system, heme metabolism, coagulation system, response to hypoxia, oxidative stress, and iron transport. Conclusion In conclusion, the combination of proteomic data with system biology platforms allowed us to amplify the information obtained processing the results and indicated the principal pathways involved. These information can point to potential biomarkers and new therapeutic targets opening the way for further analysis.